EKSPLORASI ETNOMATEMATIKA: KAJIAN KONSEP MATEMATIKA PADA PEMBUATAN LEMANG DI PONTIANAK - Supriyadi, Dede; Arasy, Siti Nurul; Wicaksono, Bayu; Jamiah, Yulis; Meldi, Nadya Febriani (Universitas Insan Budi Utomo, 2026)
Mathematics is often perceived as an abstract discipline that is detached from student’s daily lives and cultural contexts. This perception poses a challenge in mathematics education, as students frequently experience difficulties in connecting mathematical concepts with cultural contexts and real-life situations. Therefore, a meaningful and contextual learning approach is needed. This study aims to identify and describe the mathematical concepts involved in the process of making lemang in Pontianak through an ethnomathematical perspective. This research employed a descriptive qualitative method with an ethnomathematical approach. The research subjects consisted of lemang makers and sellers in Pontianak City, West Kalimantan. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive analysis model proposed by Miles and Huberman. The results show that the process of making lemang involves various activities that intuitively represent mathematical concepts, including (1) the concept of three-dimensional shapes in lemang, (2) the Pythagorean concept, (3) the concept of similarity and proportional size comparison, (4) the concept of time and production comparison, and (5) the concept of rotation in the lemang roasting process. These findings indicate that the tradition of making lemang contains mathematical values that can be integrated into learning to enhance student’s mathematical literacy and conceptual understanding in a contextual manner.